Large‐Area Smooth Conductive Films Enabled by Scalable Slot‐Die Coating of Ti3C2Tx MXene Aqueous Inks. (7th February 2023) - Guo, Tiezhu; Zhou, Di; Gao, Min; Deng, Shungui; Jafarpour, Mohammad; Avaro, Jonathan; Neels, Antonia; Hack, Erwin; Wang, Jing; Heier, Jakob; Zhang, Chuanfang (John)
Abstract: Large‐area flexible transparent conductive electrodes (TCEs) featuring excellent optoelectronic properties (low sheet resistance, Rs, at high transparency, T) are vital for integration in transparent wearable electronics (i.e., antennas, sensors, supercapacitors, etc.). Solution processing (i.e., printing and coating) of conductive inks yields highly uniform TCEs at low cost, holding great promise for commercially manufacturing of transparent electronics. However, to formulate such conductive inks as well as to realize continuous conductive films in the absence of percolation issue are quite challenging. Herein, the scalable slot‐die coating of Ti3 C2 Tx MXene aqueous inks is reported for the first time to yield large‐area uniform TCEs with outstanding optoelectronic performance, that is, average DC conductivity of 13 000 ± 500 S cm −1 . The conductive MXene nanosheets are forced to orientate horizontally as the inks are passing through the moving slot, leading to the rapid manufacturing of highly aligned MXene TCEs without notorious percolation problems. Moreover, through tuning the ink formulations, such conductive MXene films can be easily adjusted from transparent to opaque as required, demonstrating very low surface roughness and even mirror effects. These high‐quality, slot‐die‐coated MXene TCEs also demonstrate excellent electrochemical charge storage properties when assembled into supercapacitors. Abstract : Slot‐die coating enables the rapid manufacturing of highly aligned MXene Transparent Conductive Electrodes (TCEs) without notorious percolation problems. The conductive MXene nanosheets are forced to orientate horizontally as the inks are passing through the moving slot. MXene films can be easily adjusted from transparent to opaque as required, demonstrating very low surface roughness and even mirror effects.